Digital correlation of computer-generated holograms for 3D face recognition - Zhou, Haowen; Sui, Xiaomeng; Cao, Liangcai; Banerjee, Partha P (Applied optics. Optical technology and biomedical optics, 2019)
Three-dimensional (3D) face recognition has been a crucial task in human biometric verification and identification. A digital correlation method of a computer-generated hologram (CGH) for 3D face recognition is proposed, which encodes 3D data into a 2D hologram for recognition. The 3D face models are preprocessed and compressed to into groups of feature points. The CGH templates corresponding to the 3D feature points are generated by point- and layer-oriented algorithms based on three different numerical algorithms to encode depth values into 2D holograms. A 2D digital correlation is performed between the CGH templates. It is demonstrated that the generated CGHs templates could be effectively classified based on the correlation performance metrics of discrimination ratio, peak-to-correlation plane energy, and peak-to-noise ratio. With the essence of the CGH algorithm being the conversion of 3D data to a 2D hologram, the proposed encoding and decoding method has great advantages in reducing computational efforts and potential applications in 3D face recognition, storage, and display.